Contemporary higher education reform in Ecuador: Implications for faculty recruitment, hiring, and retention - Mary Amanda Johnson (Arizona State University, 2017)
Currently, there is a shortage of research on how Ecuadorian universities are coping with the contemporary reforms of higher education under the government of Correa. In 2010, La Ley Orgánica de Educación Superior (higher education law) defined the development, transparency and quality assurance of existing and new higher education institutions. This case study describes the challenges administrators have in recruiting, hiring, and retaining faculty in an environment where both fiscal and human resources are limited. The research reflects the current complexity of the higher education environment in Ecuador under contemporary reforms and creates a space for the discussion on the unique perspectives of administrators from both private and public institutions.